KAJIAN KECEPATAN TRANSFER GAS KARBONDIOKSIDA (CO2) SAAT SIKLON TROPIS DI LAUT SELATAN JAWA SECARA KLIMATOLOGI PADA BULAN MARET, APRIL, MEI TAHUN 2008 HINGGA 2020 - Ardiansyah Desmont Puryajati; Satria Ginanjar (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Meteorologi Klimatologi dan Geofisika, 2020)
Tropical cyclones can move huge amounts of heat energy from oceans into atmosphere. The transfer of heat between oceans and atmospheres is related to the transfer of CO2 gas from oceans to atmospheres. Tropical cyclones affect the absorption of CO2 into atmosphere, where wind speed and sea surface temperatures play a role in the release of CO2 into atmosphere. The study examined how tropical cyclones affect the transfer of CO2 gas from oceans to atmosphere in the Southern sea of Java in the transition season 1, which is March, April, and May starting from 2008 to 2020. The method used in the form of analysis of atmospheric and ocean dynamics uses data components of wind speed direction u and v at altitude of 10 meters as well as sea surface temperature data. The data was obtained from the ERA5 reanalysis model which is the fifth generation of ECMWF. The maximum speed of monthly CO2 transfer in March was 150 m/s, in April at 122.3 m/s, and in May at 122.3 m/s. The climatology results show that the speed of CO2 transfer is maximum when a tropical cyclone occurs in March and at least in tropical cyclones that occur in May.